2022
DOI: 10.7759/cureus.27815
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Gastrointestinal Symptoms in COVID-19 Patients in Casablanca: A Retrospective Cohort Study

Abstract: BackgroundThe novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the coronavirus disease 2019 , is behind the current pandemic. At the start of the pandemic, gastrointestinal symptoms initially described as rare were reported, but their spread to other countries increased rapidly. This study aimed to determine the prevalence of digestive symptoms among COVID-19 patients and to assess the correlation between these symptoms and disease severity. MethodsThis retrospective observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In 23 out of the examined 88 studies, [ 6 , 15 , 19 , 23 , 27 , 30 , 33 , 34 , 40 , 43 , 51 , 54 , 66 , 69 , 79 , 81 , 82 , 83 , 88 , 92 , 93 , 94 , 95 , 96 , 97 ] a COVID-19 severity assessment in patients with diarrhoea was reported. Most of the studies were conducted in China, though four papers from other countries (namely, South Korea, USA, Thailand and Singapore) have also provided such assessments.…”
Section: Resultsmentioning
confidence: 99%
“…In 23 out of the examined 88 studies, [ 6 , 15 , 19 , 23 , 27 , 30 , 33 , 34 , 40 , 43 , 51 , 54 , 66 , 69 , 79 , 81 , 82 , 83 , 88 , 92 , 93 , 94 , 95 , 96 , 97 ] a COVID-19 severity assessment in patients with diarrhoea was reported. Most of the studies were conducted in China, though four papers from other countries (namely, South Korea, USA, Thailand and Singapore) have also provided such assessments.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 The frequency of gastrointestinal symptoms vary in different studies ranging from 4.7% to 62%. 10 In a recently conducted study by Sukharani N and colleagues, 11 from Pakistan has observed overall prevalence of GI manifestation was 63.3% and among them anorexia was the most common GI manifestation (43.9%). On the other hands, GI symptoms was observed less frequent in a multicenter study from United States (18.9%) and among them diarrhea was the most common GI manifestation observed in 15.2% of the COVID-19 positive patients.…”
Section: Introductionmentioning
confidence: 97%